Primary intramedullary spinal-cord lymphoma (PISCL): a rare entity with a challenging diagnosis. Issue 5 (19th May 2021) - Martins, Emanuel Santos; Duque, Cristina; Rebelo, Olinda; Batista, Sónia
Abstract : Primary intramedullary spinal-cord lymphoma (PISCL) is a rare cause of myelopathy and constitutes only 1% of central nervous system lymphomas. Delay to diagnosis is common due to its rarity, its similarity to other causes of myelopathy and the difficulties in obtaining pathological diagnosis. We report a case of PISCL and discuss the challenges faced on diagnosis, namely the impact of corticosteroids on histological findings, the usefulness of MRI, positron-emission tomography/CT (PET/CT) and repeated lumbar punctures.